Studi Pendahuluan Pengembangan Media Game Edukasi Counting Object 1-10 Untuk Meningkatkan Kemampuan Numerasi Anak Usia 4-5 Tahun - Nida'ul Kamilatul Izza; Gunawan Gunawan; Baik Nilawati Astini; Ika Rachmayani (Indonesian Journal of Elementary and Childhood Education, 2024)
The counting object educational game is an example of an educational medium that can be utilized in learning, particularly to stimulate children's numeracy skills. Although similar media already exist, this research develops a more innovative, feasible, practical, and effective counting object educational game to enhance the numeracy skills of early childhood learners. This study aims to produce an educational game medium that can be optimally applied in teaching and learning. The method used is Research and Development (R&D) with the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The data sources for this study are children aged 4–5 years in group A, with a total of 10 children. Data collection techniques include observation, documentation, and questionnaires, with descriptive qualitative data analysis. The results of the study indicate that the developed counting object educational game is effective in improving the numeracy skills of early childhood learners after being tested with children and evaluated by media and content experts. Furthermore, satisfaction assessments of this medium show positive responses. The implication of this research is that the developed counting object educational game can be used as an effective alternative to support the development of children's numeracy skills in a learning context.